Identification of Student Misconceptions on Electrical Material Using the Certainty of Response Index (CRI) Method - Rachmat Karno Utomo; Fenny Roshayanti; Nizaruddin Nizaruddin; Harto Nuroso; Siti Patonah (Jurnal Ilmiah Pendidikan Fisika, 2025)
Students' ability to analyze abstract topics using their critical thinking skills depends on their understanding of the related concepts. Many science concepts are not well-developed, leading to misconceptions among many students. The mixed-methods approach in this study involved administering a diagnostic test within a quantitative framework, followed by the researcher providing assessments and justifications, along with each student's level of confidence. In the qualitative methodology, the researcher conducted interviews with several students to gather data on the underlying causes of misconceptions regarding electricity. Based on the overall results of the students' answers, the percentage of students who experienced misconceptions about the electricity material was 18% and was classified as low. Meanwhile, the results of the students' answers to each question showed that the percentage of misconceptions most frequently experienced by students was for question number four, which had a 38% response rate, with the question indicator explaining changes in electrical energy. According to one of the students' answers, they experienced misconceptions because the multiple-choice options provided incorrect answers, and the reasons for these incorrect answers were also incorrect. However, the student was confident in their answer, resulting in a CRI score greater than 2.5, which falls into the high category. Some students experience misconceptions because the concepts they receive from teachers are not fully understood, the learning methods used by teachers are not yet able to bridge students who have limitations in understanding and differences in learning styles, the use of textbooks by teachers in learning does not provide a comprehensive or complete explanation so that children feel they have a piecemeal understanding, and the learning activities carried out by teachers in developing skills and collaboration between students are not yet fully apparent.